Evaluation of a Dried Fermentation Product Administered Through Drinking Water on Nursery Pig Growth Performance, Fecal Consistency, and Antibiotic Injections - Alan J. Warner; Alexandra L. Gerrard; Mike D. Tokach; Raghavendra G. Amachawadi; Alain Labbé; Walter Heuser; Ramya Kalam; Xiaorong Shi; T. G. Nagaraja; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; et al. (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 350 barrows (DNA 200 × 400; initially 13.5 ± 0.02 lb) were used in a 42-d study to evaluate the effects of a dried fermentation product administered through drinking water on nursery pig growth performance, antibiotic injection frequency, fecal consistency, and fecalEscherichia colipresence. Upon arrival to the nursery research facility, pigs were randomly assigned to pens (5 pigs per pen) and pens were allotted to 1 of 2 water treatments with 35 pens per treatment. Water treatments were provided with or without a fermentation product administered through the water lines at a 1:128 dilution rate from d 0 to 14 after weaning. From d 0 to 14, 14 to 42, and for the overall experiment, there was no evidence (P>0.10) for differences observed for any growth performance criteria. There was evidence (P<0.05) for day effect on diarrhea presence. Diarrhea presence increased on d 4 and 6, then decreased to low levels. There was no evidence for the fermentation product to influence diarrhea incidence. For antibiotic injections, there was no evidence (P>0.10) for differences observed between treatments. Mortalities were low, with no evidence (P>0.10) for differences observed between treatments for removals or mortalities. For fecal dry matter on d 7 and 14, there was no evidence (P>0.10) for differences observed between treatments. In summary, under these experimental conditions, administering a dried fermentation product for the first 14 d in the nursery through the drinking water did not improve growth performance, fecal dry matter, diarrhea presence, antibiotic injections, or removals and mortalities in nursery pigs. Further evaluation of the dried fermentation product in commercial facilities with greater diarrhea and mortality is needed.
Keywords: dried fermentation product; fecal dry matter; growth; nursery pig